Penyuluhan Model Pendampingan dan Perubahan Status Gizi Anak Usia 6 – 24 Bulan - Aswita Amir; S. Fatimah Muis; Suyatno Suyatno (MEDIA MEDIKA INDONESIANA, 2008)
The outreach counseling model and nutritional status change in 6–24 months old childrenBackground: Insufficient knowledge on food and health of mothers will lead to inadequate food intake and high infection risk, especially diarrhea and acute respiratory tract infection (ARTI). Improvement of knowledge can be achieved by counseling. There are several model of counseling, one of them is the outreach model. This study aimed was to analyze the influence of outreach counseling model toward the change of nutritional status of 6–24 months old children. Methods: Research design was a quasi experiment with non randomized pre post test control group. Intervention group recieved outreach counseling model by outreach nutritionists (Tenaga Gizi Pendamping) and control group recieved conventional counseling from nutritionists of primary health care center (Tenaga Gizi Puskesmas). The study was done in Makassar City, South Sulawesi Province with the working area of Sudiang Raya’s Primary Health Care chosen as intervention area and Bira’s Primary Health Care as control site. Subjects were children aged 6–24 months with WAZ between -3 until 0 SD. The number of subjects in intervention group were 32 and control were 37 children. The observation variables were changes of mother’s knowledge, energy adequacy level, protein adequacy level, diarrhea and ARTI duration and nutritional status (WAZ, HAZ and WHZ) of the children. Data were analyzed using t-test and multivariate analysis by linear regression.Results: After 3 months of intervention, there were increase in mother’s knowledge, energy adequacy level, and the decrease of duration diarrhea was higher in the outreach counseling group than the control group. The WAZ and HAZ in outreach counseling group were better than control group, and there was an increase in WHZ in outreach counseling group with a decrease in the control group.Conclusions: Outreach counseling model is more effective than conventional counseling in lowering the decrease of nutritional status on 6–24 months old children.Key words: Outreached counseling, nutritional status, 6–24 months old children. ABSTRAK Latar Belakang: Pengetahuan ibu yang kurang tentang gizi dan kesehatan akan menyebabkan asupan makanan yang tidak cukup serta meningkatnya risiko penyakit infeksi diantaranya diare dan ISPA pada anak. Peningkatan pengetahuan dapat dilakukan dengan penyuluhan. Penyuluhan terdiri dari beberapa model, salah satu diantaranya adalah model pendampingan. Penelitian ini bertujuan untuk menganalisis pengaruh penyuluhan model pendampingan terhadap ibu selama 3 bulan terhadap perubahan status gizi anak usia 6-24 bulan.Metode: Desain penelitian adalah quasi experiment berupa non randomized pre post test control group. Kelompok intervensi mendapat penyuluhan model pendampingan oleh Tenaga Gizi Pendamping (TGP) dan kelompok kontrol mendapat penyuluhan konvensional oleh Tenaga Gizi Puskesmas. Penelitian dilakukan di wilayah kerja Puskesmas Sudiang Raya Kota Makassar sebagai lokasi intervensi dan Puskesmas Bira sebagai lokasi kontrol. Subyek penelitian adalah anak usia 6–24 bulan dengan skor Z BB/U -3 s.d. 0 SB. Jumlah subyek untuk kelompok intervensi 32 dan kontrol 37 anak. Variabel yang diamati meliputi perubahan pengetahuan ibu, Tingkat Kecukupan Energi (TKE), Tingkat Kecukupan Protein (TKP), hari sakit (Diare dan ISPA) dan status gizi (skor Z BB/U, PB/U dan BB/PB). Analisis data dilakukan dengan menggunakan uji beda dan analisis multivariat dengan regresi linier.Hasil: Setelah 3 bulan intervensi, terjadi peningkatan rerata skor pengetahuan ibu dan TKE, dan penurunan jumlah hari sakit diare lebih tinggi pada kelompok intervensi dibandingkan kontrol. Status gizi (skor Z BB/U dan PB/U) pada kelompok intervensi lebih baik dibandingkan kontrol (p<0,05), terjadi peningkatan skor Z BB/PB pada kelompok intervensi dan penurunan skor tersebut pada kelompok kontrol (p<0,05).Simpulan: Penyuluhan model pendampingan lebih efektif daripada penyuluhan konvensional dalam menekan penurunan status gizi anak usia 6–24 bulan.